2013
DOI: 10.7314/apjcp.2013.14.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Perspective of T1799A BRAF Mutation Diagnostic Value in Papillary Thyroid Carcinoma

Abstract: Background: Throughout Indonesia, thyroid cancer is one of the ten commonest malignancies, with papillary thyroid carcinoma (PTC) in our hospital accounting for about 60% of all thyroid nodules. Although fine needle aspiration biopsy (FNAB) is the most reliable diagnostic tool, some nodules are diagnosed as indeterminate and second surgery is common for PTC. The aim of this study was to establish the diagnostic value and feasibility of testing the BRAF T1799A mutation on FNA specimens for improving PTC diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…Furthermore, multiple previous studies have demonstrated a correlation between the BRAF (V600E) mutation and the high-risk clinicopathological characteristics of PTC, including older age at diagnosis, male gender, large tumor size, the presence of extrathyroidal extension, lymph node and distant metastasis and an advanced stage (9)(10)(11)13,15,16,(18)(19)(20)28,29). By contrast, certain studies were unable to identify marked associations between the BRAF (V600E) mutation and the high-risk clinicopathological characteristics of PTC (12,14).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, multiple previous studies have demonstrated a correlation between the BRAF (V600E) mutation and the high-risk clinicopathological characteristics of PTC, including older age at diagnosis, male gender, large tumor size, the presence of extrathyroidal extension, lymph node and distant metastasis and an advanced stage (9)(10)(11)13,15,16,(18)(19)(20)28,29). By contrast, certain studies were unable to identify marked associations between the BRAF (V600E) mutation and the high-risk clinicopathological characteristics of PTC (12,14).…”
Section: Discussionmentioning
confidence: 94%
“…Numerous studies have evaluated the association between the BRAF (V600E) mutation, clinicopathological features and clinical outcomes of PTC; however, controversial results have been obtained for a correlation between the BRAF (V600E) mutation and clinicopathological features (1,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Furthermore, multiple previous studies have demonstrated a correlation between the BRAF (V600E) mutation and the high-risk clinicopathological characteristics of PTC, including older age at diagnosis, male gender, large tumor size, the presence of extrathyroidal extension, lymph node and distant metastasis and an advanced stage (9)(10)(11)13,15,16,(18)(19)(20)28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Papillary carcinoma growth is stimulated by thyroidstimulating hormone and the carcinomas can be shrunk with thyroid hormones. Eighty percent of PTC patients survive approximately 10 years (Brahma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Medullary thyroid carcinomas (MTC) are derived from the parafollicular C-cells, they account for a minority (5%) of thyroid carcinomas. V600E mutations in papillary thyroid carcinoma occurred more than 50% in Iran and Indonesia (Brahma et al, 2013;Ranjbar et al, 2013). This spectrum of progression has been linked with a pattern of cumulative genetic defects that correlate with tumor differentiation, metastatic potential, and aggressiveness.…”
Section: Introductionmentioning
confidence: 99%